Menggali Nilai-Nilai dan Hakikat Wanita Dalam Pandangan Ki Hadjar Dewantara - Dyah Kumalasari (ISTORIA: Jurnal Pendidikan dan Sejarah, 2017)
AbstractThis study aims to analyze more about the nature of women in the view of Ki Hadjar Dewantara and what values can be developed in the process of learning in the course of History of Women. This research is designed to use critical historical methods. Critical historical methods include the process of collecting, testing, analyzing the source with criticism both internally and externally, then interpreted and presented in the form of writing history. Four procedures in the process of historical research follow the steps of historical writing as follows: heuristics, verification, interpretation, and historiography. The result of the research explains that Ki Hadjar Dewantara idea and thought is based on cultural and religious background and loaded with eastern values so that it can balance the study of feminism which mostly raises the ideas of women movement from Western concept and is often less culturally appropriate East. That women are naturally different from men both physically and psychologically. However, women still have to get the same rights in education. Women should be forward-thinking and educated in order to properly educate their sons. Women are also not prohibited for a career, but must still adjust to the nature of her femininity. Careers suitable for women according to Ki Hadjar Dewantara is in the field of education, medical, and art. Keywords: values, essence of woman, emancipation, feminism, History of woman